1997
DOI: 10.1002/(sici)1099-114x(199701)21:1<21::aid-er231>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Butanol—a Single Cylinder Engine Study: Engine Performance

Abstract: SUMMARYThe effect of methanol and butanol addition to gasoline on brake specific fuel consumption (b.s.f.c.), exhaust gas temperature, and thermal efficiency has been experimentally investigated. A Hydra single cylinder, spark ignition, fuel injection engine was used over a wide range of fuel/air equivalence ratio ("0·8 to 1·3) for 30% volume alcohol-gasoline blends. The goal of this work is to study the engine performance when methanol and butanol-gasoline blends are used. The performance measurements show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…For example the studies of Brinkman (1981), , Davis and Heil (2000), Al-Farayedhi et al (2004), Nakata et al (2006), andTopgül et al (2006) focused on performance characteristics, while the works of Guerrieri et al (1995), , Sandiquist et al (2001), and Martinez and Ganji (2006) on exhaust emission measurements. Similarly, the combustion of butanol=gasoline blends with PFI was investigated by Alasfour (1997) and Swaja and Naber (2010) in single-cylinder research engines. In an attempt to bridge the gap of our understanding between PFI and direct injection (DI) of alcohols, Zhu et al (2008) reported on the combustion characteristics of ethanol on a single cylinder dual-fuel injection spark ignition (SI) engine with the following fueling cases: (a) gasoline PFI and DI, (b) gasoline PFI and ethanol DI, and (c) ethanol PFI and gasoline DI.…”
Section: Introductionmentioning
confidence: 99%
“…For example the studies of Brinkman (1981), , Davis and Heil (2000), Al-Farayedhi et al (2004), Nakata et al (2006), andTopgül et al (2006) focused on performance characteristics, while the works of Guerrieri et al (1995), , Sandiquist et al (2001), and Martinez and Ganji (2006) on exhaust emission measurements. Similarly, the combustion of butanol=gasoline blends with PFI was investigated by Alasfour (1997) and Swaja and Naber (2010) in single-cylinder research engines. In an attempt to bridge the gap of our understanding between PFI and direct injection (DI) of alcohols, Zhu et al (2008) reported on the combustion characteristics of ethanol on a single cylinder dual-fuel injection spark ignition (SI) engine with the following fueling cases: (a) gasoline PFI and DI, (b) gasoline PFI and ethanol DI, and (c) ethanol PFI and gasoline DI.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to use a very wide range of raw materials for producing bioethanol (on the contrary to producing biodiesel fuel) including cereal and corn grains, sugar beets, molasses, potatoes as well as raw materials containing lignocellulose -wood and wood waste, rapidly growing ligneous plants, cereal and rape straws etc. (Festel 2006;Ramey and Yang 2004;Alasfour 1997;Maddox and Murray 1983). An enormous potential of raw materials makes searching for the substitutes of bioethanol that could be made from the same raw materials without increasing material and energetic expenditure and cost price.…”
Section: Introductionmentioning
confidence: 99%
“…2007;Labeckas et al 2006;Raslavičius and Markšaitis 2007;Hsieh et al 2002;Bilgin et al 2002;Al-Hasan 2003;Satgé de Caro et al 2001;Abu-Quadais et al 2000;Gautam et al 2000;Choi and Reitz 1999;Ajav et al 1998 and1999 etc.). A limited number of studies have been previously undertaken to evaluate the suitability of iso-butanol as an alternative fuel for spark ignition engines (Andziulis 2006;Alasfour 1997;Popuri and Bata 1993;Rice et al 1991;Bata et al 1989a and1989b). Most of these studies have shown that alcohol fuels can have a level of performance comparable to that of diesel and gasoline fuels.…”
Section: Introductionmentioning
confidence: 99%